FINANCIAL PERFORMANCE ANALYSIS OF PT. SUPARMA TBK YEAR 2022-2023 USING ACTIVITY RATIO - Hargo Dedali, Shindu (Ecopreneur.12, 2024)
The urgency of this research is how optimal income and cash are seen from the efficiency of company assets for the Financial Performance of PT. Suparma Tbk in 2022-2023, if viewed using Activity Ratios. Also research like this has the aim of looking at the Financial Performance of PT. Suparma Tbk, if viewed from the Activity side, uses this Activity Ratio for 2022-2023, so that Finance is useful for Investors who want to buy Shares in PT. Suparma Tbk what is the financial condition of PT. Suparma Tbk is in good health. These studies are qualitative descriptive research. For this research data, researchers obtained from the Financial Report of PT. Suparma Tbk in 2022-2023. Data analysis is from calculating the Activity ratio using the formula Total Asset Turnover Ratio & Fixed Asset Turnover Ratio.